How to find the general solution of the equation tan θ = 0?
Prove that the general solution of tan θ = 0 is θ = nπ, n ∈ Z.
Solution:
According to the figure, by definition, we have,
Tangent function is defined as the ratio of the side perpendicular divided by the adjacent.
Let O be the centre of a unit circle. We know that in unit circle, the length of the circumference is 2π.If we started from A and moves in anticlockwise direction then at the points A, B, A', B' and A, the arc length travelled are 0, \(\frac{π}{2}\), π, \(\frac{3π}{2}\), and 2π.
tan θ = \(\frac{PM}{OM}\)
Now, tan θ = 0
⇒ \(\frac{PM}{OM}\) = 0
⇒ PM = 0.
So when will the tangent be equal to zero?
Clearly, if PM = 0 then the final arm OP of the angle θ coincides with OX or OX'.
Similarly, the final arm OP coincides with OX or OX' when θ = π, 2π, 3π, 4π, ……….. , - π, -2π, -3π, -4π, ……….. i.e. when θ an integral multiples of π i.e., when θ = nπ where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
Hence, θ = nπ, n ∈ Z is the general solution of the given equation tan θ = 0
1. Find the general solution of the equation tan 2x = 0
Solution:
tan 2x = 0
⇒ 2x = nπ, where, n = 0, ± 1, ± 2, ± 3, ……. [Since, we know that the general solution of the given equation tan θ = 0 is nπ, where, n = 0, ± 1, ± 2, ± 3, ……. ]
⇒ x = \(\frac{nπ}{2}\), where, n = 0, ± 1, ± 2, ± 3, …….
Therefore, the general solution of the trigonometric equation tan 2x = 0 is
x = \(\frac{nπ}{2}\), where, n = 0, ± 1, ± 2, ± 3, …….
2. Find the general solution of the equation tan \(\frac{x}{2}\) = 0
Solution:
tan \(\frac{x}{2}\) = 0
⇒ \(\frac{x}{2}\) = nπ, where, n = 0, ± 1, ± 2, ± 3, ……. [Since, we know that the general solution of the given equation tan θ = 0 is nπ, where, n = 0, ± 1, ± 2, ± 3, ……. ]
⇒ x = 2nπ, where, n = 0, ± 1, ± 2, ± 3, …….
Therefore, the general solution of the trigonometric equation tan \(\frac{x}{2}\) = 0 is
x = 2nπ, where, n = 0, ± 1, ± 2, ± 3, …….
3. What is the general solution of the equation tan x + tan 2x + tan 3x = tan x tan 2x tan 3x?
Solution:
tan x + tan 2x + tan 3x = tan x tan 2x tan 3x
⇒ tan x + tan 2x = - tan 3x + tan x tan 2x tan 3x
⇒ tan x + tan 2x = - tan 3x(1 - tan x tan 2x)
⇒ \(\frac{tan x + tan 2x}{1 - tan x tan 2x}\) = - tan 3x
⇒ tan (x + 2x) = - tan 3x
⇒ tan 3x = - tan 3x
⇒ 2 tan 3x = 0
⇒ tan 3x = 0
⇒ 3x = nπ, where n = 0, ± 1, ± 2, ± 3,…….
x = \(\frac{nπ}{3}\), where n = 0, ± 1, ± 2, ± 3,…….
Therefore, the general solution of the trigonometric equation tan x + tan 2x + tan 3x = tan x tan 2x tan 3x is x = \(\frac{nπ}{3}\), where n = 0, ± 1, ± 2, ± 3,…….
4. Find the general solution of the equation tan \(\frac{3x}{4}\) = 0
Solution:
tan \(\frac{3x}{4}\) = 0
⇒ \(\frac{3x}{4}\) = nπ, where, n = 0, ± 1, ± 2, ± 3, ……. [Since, we know that the general solution of the given equation tan θ = 0 is nπ, where, n = 0, ± 1, ± 2, ± 3, ……. ]
⇒ x = \(\frac{4nπ}{3}\), where, n = 0, ± 1, ± 2, ± 3, …….
Therefore, the general solution of the trigonometric equation tan \(\frac{3x}{4}\) = 0 is x = \(\frac{4nπ}{3}\), where, n = 0, ± 1, ± 2, ± 3, …….
11 and 12 Grade Math
From tan θ = 0 to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Aug 10, 24 04:59 PM
Aug 10, 24 02:25 AM
Aug 10, 24 01:59 AM
Aug 10, 24 01:57 AM
Aug 06, 24 02:12 AM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.